2013
DOI: 10.4025/actasciagron.v35i1.15066
|View full text |Cite
|
Sign up to set email alerts
|

Growing Princesa apples under semiarid conditions in northeastern Brazil

Abstract: ABSTRACT. Phenological observations are some of the most sensitive data for the identification of plant species growth in regional climate conditions. Thus, an experiment was conducted from October 2008 to December 2009 to characterize the phenological stages, fruit set and fruit yield of Princesa apples grown under a semiarid climate in northeastern Brazil. Phenological data (stages) were determined in the orchard by daily observations from bud breaking until fruit ripening. The following variables were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…The average fruit productions contained in Table 3 Following the same tendency of the fruit production (kg plant -1 ), fruit yield was also significantly higher (18%) for 'Princesa' cv. Both apple cultivars studied presented fruit yield, in average, higher than those quoted in the scientific literature by Lopes et al (2012) and Lopes et al (2013) who reported 10.3 t ha -1 and 12.73 t ha -1…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…The average fruit productions contained in Table 3 Following the same tendency of the fruit production (kg plant -1 ), fruit yield was also significantly higher (18%) for 'Princesa' cv. Both apple cultivars studied presented fruit yield, in average, higher than those quoted in the scientific literature by Lopes et al (2012) and Lopes et al (2013) who reported 10.3 t ha -1 and 12.73 t ha -1…”
Section: Resultscontrasting
confidence: 40%
“…The Princesa apples plants of the present study produced more fruits than those evaluated by Lopes et al (2013) and Chagas et al (2012), while Eva apples promoted a number of fruits higher than Lopes et al (2012) but lower than Chagas et al (2012).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The phenological behavior of the pear tree variety 'Princesinha' was evaluated through visual observations made daily from the pruning and application of Dormex ® until the harvest as recommended by Lopes et al (2013b). For phenological analysis, 5 plants were randomly selected in which 4 branches were selected, each one being distributed, totaling 20 branches.…”
mentioning
confidence: 99%
“…All 128 orchard plants were used for the quantification of the production, which was based on the methodology by Lopes et al (2013b) that evaluated the following production variables: I) plant germination (%): relationship between number of flowers (of all corymb present in the selected branches) and number of fruits (%); ii) number of fruits per plant; iii) fruit production per plant (kg) measured using a precision scale (Filizola ® brand, model CF15, with 0.5 g precision); and iv) productivity obtained by multiplying the production of fruits per plant and total number of plants in one hectare.…”
mentioning
confidence: 99%